The Effect Of Price Competition And Trust On Electronic Product Purchase Decisions On Outlet Offline and Online Retail - Agitha, Agitha; Dahlan, Kandi Sofia Senastri (Al-Makki Publisher, 2023)
This study aims to examine the effect of price competition and trust on electronic product purchase decisions at offline and online retail outlets. This type of research is quantitative research, using the Partial Least Square Structural Equation Modeling method or called PLS-SEM because it is one of the variant-based tools that simultaneously measure relationships between variables and test measurement models as well as structural model testing with the help of SmartPLS software. The method used in this study is the survey method, where the author distributes questionnaires for data collection. The population used is consumers who have purchased electronic products both offline and online, especially in the Tangerang Banten area, with a sample of 248 used. This study uses price and trust variables as independent variables, electronic product purchase decisions as dependent variables, and offline retail outlets and online retail outlets as intervening variables. The results of this study show that Price has a positive and significant effect on Electronic Product Purchase Decisions, Prices have a positive and significant effect on Offline and Online Retail Outlets, Trust has a positive and significant effect on Electronic Product Purchase Decisions, Trust has a positive and significant effect on Offline and Online Retail Outlets, Offline Outlets and Online Retail have a positive and significant effect on Electronic Product Purchase Decisions.